Instrumented mouthguards in elite-level men's and women's rugby union: the incidence and propensity of head acceleration events in matches - Tooby, J.; Woodward, J.; Tucker, R.; Jones, B.; Falvey, E.; Salmon, D.; Dawn Bussey, M.; Starling, L.; Tierney, G. (Sports Medicine, 2024)
Objectives: The aim of this study was to examine head acceleration event (HAE) propensity and incidence during elite-level men`s and women`s rugby union matches. Methods: Instrumented mouthguards (iMGs) were fitted in 92 male and 72 female players from nine elite-level clubs and three international teams. Data were collected during 406 player matches (239 male, 167 female) using iMGs and video analysis. Incidence was calculated as the number of HAEs per player hour and propensity as the proportion of contact events resulting in an HAE at a range of linear and angular thresholds. Results: HAE incidence above 10 g was 22.7 and 13.2 per hour in men`s forwards and backs and 11.8 and 7.2 per hour in women`s forwards and backs, respectively. Propensity varied by contact event, with 35.6% and 35.4% of men`s tackles and carries and 23.1% and 19.6% of women`s tackles and carries producing HAEs above 1.0 krad/s2. Tackles produced significantly more HAEs than carries, and incidence was greater in forwards compared with backs for both sexes and in men compared with women. Women's forwards were 1.6 times more likely to experience a medium-magnitude HAE from a carry than women's backs. Propensity was similar from tackles and carries, and between positional groups, while significantly higher in men than women. The initial collision stage of the tackle had a higher propensity than other stages. Conclusion: This study quantifies HAE exposures in elite rugby union players using iMGs. Most contact events in rugby union resulted in lower-magnitude HAEs, while higher-magnitude HAEs were comparatively rare. An HAE above 40 g occurred once every 60-100 min in men and 200-300 min in women. Future research on mechanisms for HAEs may inform strategies aimed at reducing HAEs.